The α-casein gene polymorphism of goats in tropical environment - Mohammed, M.T.A.; Dhuha, J. M.; Haniza, M.Z.H.; Al-Bakri Salih, A. (Diponegoro University, 2019)
This study was completed to investigate the breed factor that influences milk production in different goat breeds in the tropical environmental area. A total of 28 goats were utilized in this work. These goats consisted of two different breeds, which were Anglo-Nubian and Saanen. Blood samples were withdrawn through jugular veinsof goats into plastic tubes without EDTA for gene polymorphism. A t-test was used to analyse if there are any significant differences in molecular weight and frequency values of DNA between breeds. Investigation of DNA polymorphism in alleles A, B and C of α-casein were identified in all breeds, while allele F were studied in Saanen goats only. As a conclusion; Saanen goats have more varieties α-casein allele